PREDIKSI AKTIVITAS INHIBISI DAN TOKSISITAS BEBERAPA SENYAWA DALAM BUAH TIN (FICUS CARICA L.) SEBAGAI ANTIVIRUS SECARA IN SILICO - Khonsa
Viral infection is a global health problem that can cause endemic to pandemic. Compounds delivered from plants has been developed as an alternative antiviral agent. One of the plants that has been used traditionally as antiviral therapy is Ficus carica L. (figs). The aim of this research is to predict the inhibitory activity and toxicity of compounds contained in figs as an antiviral for influenza A, HIV, and dengue viruses using in silico method. Compounds were docked to the PA- CTD of H1N1 (PBD ID: 5IEQ), PB2 of H3N2 (PDB ID: 4NCM), HIV-1 RT (PDB ID: 3LAL), and DENV-3 RdRp NS5 (PDB ID: 3VWS) protein. Three-dimentional structures were modeled using GaussView and optimized using Gaussian 09W. Optimized compounds were docked to the target protein using AutoDock Tools and the interaction to protein binding side were analyzed in comparison with the standard compounds. The standard compound used for the analysis was 1-(4-chlorophenyl)-1Himidazole for PA-CTD H1N1, pimodivir for PB2 H3N2, nevirapine, efavirenz, and doravirine for HIV1 RT, and 5-{[(4-chlorophenyl)sulfonyl]amino}-2-methyl-1-benzofuran-3-carboxylic acid for DENV-3 RdRp NS5. The compound toxicity was analyzed using ECOSAR and Toxtree. Based on the results, the compounds that has similar interaction to the standard compounds were psoralen for PA-CTD H1N1 protein with 4 similar hydrophobic interactions, (-)-epicatechin for PB2 of H3N2 protein which has 3 hydrogen bonds with GLU361, SER324, and LYS376, campesterol for HIV-1 RT protein which has 4 similar hydrophobic interactions, and (+)-catechin for DENV-3 RdRp NS5 protein which has a hydrogen bond with GLY604. Based on the classification of Cramer Rules for toxicity test, all four compounds are classified in class 3 (high toxicity) and according to the Benigni/Bossa Rulebase classification, all four compounds are negative for genotoxic and nongenotoxic carcinogenicity except psoralen is predicted to be genotoxic carcinogenicity.